Use of UVC radiation as a postharvest stressor to increase phenolic compounds concentration and antioxidant status in purple, orange, and white carrots - Valerga, Lucia (2024)
Previous studies have demonstrated that postharvest UVC radiation can increase antioxidant status in orange carrots, but the response to UVC in other carrot colors is unclear. This study investigated the effect of postharvest UVC radiation (8 kJ m 2) on the concentration of total phenolics (TP), total hydroxycinnamic acids (HI), chlorogenic acid (CGA), anthocyanin content and composition, and antioxidant capacity (AOX) in whole-, peeland sliced roots of an orange-, a white-, and three purple-rooted cultivars during storage at 20 ◦C. Results revealed that the UVC radiation, the root color phenotype, the carrot genotype within a particular root color, the degree of root processing, the storage time, and the type and color of individual root tissues all influenced TP, HI, CGA, and AOX levels, but not anthocyanin content and composition. UVC radiation significantly increased the level of non-anthocyanin phenolics (p < 0.05) up to 2.9, 2.8, 2.3, and 2.6-folds (reaching TP concentrations of 2694–4767 mg kg 1, depending on the cultivar, with HI and CGA accounting for 83–100% and 40–44% of the TP content, respectively); and AOX up to 2.4, 1.9, 2.2, and 2.7-folds, relative to UVC-untreated controls, for orange, white, purple-orange, and purple-yellow carrots, respectively. Conversely, a cultivar with solid purple root revealed no increase in phenolics and AOX levels due to the UVC. Tissue-specific analysis in UVC-treated slices of orange and purple-orange carrots evidenced differences between the outer and inner root tissues, as well as between purple and orange tissues of the same root, revealing significant increases in phenolics and AOX levels in orange but not purple tissue. Additional experiments that examined the role of anthocyanins in the carrot response to UVC revealed that these pigments inhibited the UVC-induced upregulation of phenolic acids biosynthesis in a dose-dependent fashion, presumably due their photoprotective roles as antioxidant and lightabsorbing agents. Altogether, our data suggest variable potential for increasing nutraceutical value in different carrot colors by UVC radiation.